Optimization of Resource Utilization of Fast Fourier Transform - Subhash Chandra Yadav; Pradeep Juneja; R. G. Varshney (Institute of Advanced Engineering and Science, 2017)
This paper considers the optimization of resource utilization for three FFT algorithms, as it pertains not to the input samples or output modes, but to the twiddle factors that arise in Cooley-Tukey FFT algorithms. Twiddle factors are a set of complex roots of unity, fixed by the transform order for the particular algorithm. This paper shows the comparison between three known FFT algorithms, DIT-FFT, DIF-FFT and GT algorithm. All these algorithms are implemented on FPGA (Spartan-3 XC3S4000l-4fg900) with XILINX 10.1 ISE.